An Extended Discrete Model for Actuarial Data and Value at Risk Analysis: Properties, Applications and Risk Analysis under Financial Automobile Claims Data - Ibrahim, Mohamed; Butt, Nadeem Shafique; Al-Nefaie, Abdullah H.; Hamedani, G. G.; Yousof, Haitham M.; Mahmoud, Aya Shehata (Statistics, Optimization & Information Computing, 2024)
This paper deals with a new discrete distribution with high flexibility. We have studied many of its mathematical and statistical properties, and we have neglected many other properties due to the narrow scope of the paper. Additionally, we have presented a comprehensive analysis of actuarial risks. A good set of actuarial risk indicators that are used in financial analysis and measurement and evaluation of financial risks. Five discrete data sets have been relied upon in conducting the financial analysis and risk assessment. Necessary comments have been provided on the results of the paper, and a set of necessary recommendations are provided for insurance companies to avoid the occurrence of unexpected large losses. All these financial analyses have been conducted in light of a discrete probability distribution.